Hydrogen isotope fractionation in the system brucite-water ± NaCl to elevated temperatures and pressures: Implications for the isotopic property of NaCl fluids under geologic conditions. (15th August 2018) - Horita, Juske; Driesner, Thomas; Cole, David R.
Abstract: A series of hydrothermal experiments have been conducted to determine equilibrium D/H fractionations between brucite and water as a function of temperature (200–600 °C), pressure (2.1–800 MPa), and dissolved NaCl (0–5 molal or 0–22.6 wt%). Along with our previous study, a total of 39 data points show that pressure and dissolved NaCl both increase the D/H fractionation factor at a given temperature. Theoretical treatment allowed a first direct comparison of experimental and theoretical results of brucite-water D/H fractionation at a zero pressure limit. After correcting the pressure effects on brucite D/H partition function ratios (β-factor), the isotope effects of pressure and dissolved NaCl on the D/H β-factor of water were for the first time rigorously evaluated. There is a good linear relationship between the D/H β-factor of the aqueous NaCl solutions and their densities of at a given temperature. A good, pseudo-linear relationship observed between the density of aqueous NaCl solutions and the maximum intensity of the asymmetric OH vibrational frequency of water in turn suggests that this frequency is a fundamental property that determines the β-factor of water at elevated temperatures and pressures. Our study suggests that the density of aqueous solutions ( ρ aq - soln ) could be used as a primary parameter to predict the effects of pressure and NaCl compositions on the β-factor of water under geologic conditions encountered in the crust and upper mantle: Δ 10 3 ln β wat / Δ ρ aq - soln  = −0.0111 (±0.0012), where Δ is a difference in the value of 10 3 ln β wat or ρ aq - soln, and ρ aq - soln in kg m −3 .